2020
DOI: 10.7150/thno.45903
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-guided sonopermeation of neuroblastoma: a novel strategy for monitoring and predicting liposomal doxorubicin uptake in vivo

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor in infants and children, and imposes significant morbidity and mortality in this population. The aggressive chemoradiotherapy required to treat high-risk NB results in survival of less than 50%, yet is associated with significant long-term adverse effects in survivors. Boosting efficacy and reducing morbidity are therefore key goals of treatment for affected children. We hypothesize that these may be achieved by developing strategies that both focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…This approach is known as sonopermeation, which helps to increase vascular permeability and thus increased penetration of drugs into the target tissue 323 . A report by Bellary et al 324 has described a novel 2D and 3D quantitative contrast‐enhanced ultrasound imaging (qCEUS) system that could be used to monitor the therapeutic efficacy of sonopermeation in NB tumors. That study has also found that combing ultrasound therapy with UCA significantly enhances the doxorubicin payload to NB in an orthotopic xenograft model, and qCEUS imaging indicates that there is significant doxorubicin uptake induced by increasing the tumor vascular permeability (reduced pericyte coverage) due to microbubble sonopermeation, with no damage to vasculature 324 .…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is known as sonopermeation, which helps to increase vascular permeability and thus increased penetration of drugs into the target tissue 323 . A report by Bellary et al 324 has described a novel 2D and 3D quantitative contrast‐enhanced ultrasound imaging (qCEUS) system that could be used to monitor the therapeutic efficacy of sonopermeation in NB tumors. That study has also found that combing ultrasound therapy with UCA significantly enhances the doxorubicin payload to NB in an orthotopic xenograft model, and qCEUS imaging indicates that there is significant doxorubicin uptake induced by increasing the tumor vascular permeability (reduced pericyte coverage) due to microbubble sonopermeation, with no damage to vasculature 324 .…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 99%
“…A report by Bellary et al 324 has described a novel 2D and 3D quantitative contrast‐enhanced ultrasound imaging (qCEUS) system that could be used to monitor the therapeutic efficacy of sonopermeation in NB tumors. That study has also found that combing ultrasound therapy with UCA significantly enhances the doxorubicin payload to NB in an orthotopic xenograft model, and qCEUS imaging indicates that there is significant doxorubicin uptake induced by increasing the tumor vascular permeability (reduced pericyte coverage) due to microbubble sonopermeation, with no damage to vasculature 324 . Overall, ultrasound‐based approaches already have a significant impact on the diagnosis and management of NB, and may also be useful for the treatment of NB.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 99%
“…In vivo drug delivery studies were performed with PDLCs in Matrigel™ plug “mock” tumors. The Matrigel™ was implanted in Female CD-1 mice (Charles River, Wilmington, MA) as outlined previously by Bellary et al [ 58 ]. Briefly, 10 mL of frozen Matrigel™ was thawed overnight on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Sonication was applied for 8 min, turning the transducer on/off every 5 s to allow reflow of fresh PDLCs. Matrigel™ plugs were surgically excised for ex vivo analysis 20 min after PDLC injection, as described by Bellary et al [ 58 ]. Excised plugs were frozen using dry ice-cooled 2-methyl butane (Sigma Aldrich, St. Louis, MO, USA) and kept in tubes in freezer (−80 °C).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Yousefian and colleagues showed a tumor growth delay of murine breast cancer after a combination of bleomycin injection and microbubble-assisted ultrasound, compared to untreated, bleomycin alone or ultrasound alone treated tumors 6 . Besides small therapeutic molecules like bleomycin, it could be demonstrated that the co-administration of microbubbles and doxorubicin loaded liposomes with a size of approximately 100 nm in combination with ultrasound could enhance the liposome accumulation in a mouse neuroblastoma tumor model 2 and improve the treatment response of murine colorectal cancer 7 . In a first clinical phase I study, pancreatic ductal adenocarcinoma patients treated with microbubble-assisted ultrasound could receive a higher number of treatment cycles with gemcitabine compared to a historical cohort treated with gemcitabine alone.…”
Section: Introductionmentioning
confidence: 99%